Remittances and Expenditure Patterns of the Left Behinds in Rural China - Sylvie Démurger; Xiaoqian Wang (Institute for the Study of Labor (IZA), 2016)
This paper investigates how private transfers from internal migration in China affect the expenditure behaviour of families left behind in rural areas. Using data from the Rural-Urban Migration in China (RUMiC) survey, we assess the impact of remittances sent to rural households on consumption-type and investment-type expenditures. We apply propensity score matching to account for the selection of households into receiving remittances, and estimate average treatment effects on the treated. We find that remittances supplement income in rural China and lead to increased consumption rather than increased investment. Moreover, we find evidence of a strong negative impact on education expenditures, which could be detrimental to sustaining investment in human capital in poor rural areas in China.
Keywords: O15; J22; R23; D13; O53; 330; remittances; labour migration; expenditure behaviour; left-behind; China; propensity score matching